THE EFFECT OF SERIAL IMAGE MEDIA ON STUDENTS' ABILITY TO WRITE NARRATIVE ESSAYS ON THEMATIC LEARNING MODELING - Sitti Aminah; Widia Tamara; Meri Hari Yanni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The effect of serial image media on students' ability to write narrative essays on thematic learning modeling. Sitti Aminah, Bumi Persada University. Writing is a form of manifestation of language abilities and skills most recently mastered by students. Serial image media used in writing narrative essays is a series of images arranged chronologically. This research was conducted using quantitative methods with a pseudo-experimental approach. The formulation of the problem in this study is whether the ability to write narrative essays of seventh grade students of SMPN 2 Samudra is good. The purpose of this study was to find out the effect of using serial picture media on the ability of seventh grade students of SMPN 2 Samudra in writing narrative essay. This research was conducted using observation, interview, and test techniques at the end of the lesson. Based on the results of observations and the research process that researchers carry out, it is known that the ability of students in writing narrative essays is very low due to the absence of media or learning methods used in the learning process. This is due to the absence of knowledge of learning development by educators at the school. The results showed the influence of serial image media in the learning process in the experimental class. So that students' ability to relate other learning to write narrative essays increases. In conclusion, learning media determines the success and improves children's cognitive abilities.